Kearifan Ekologi dalam Cerita Rakyat Sumatera Selatan - Sarwo Edi, Basuki; Wardarita, Ratu (International Seminar on Austronesian Languages and Literature, 2021)
This study aims to describe (1) the forms of ecological wisdom contained in the folklore of South Sumatra, (2) the interaction of characters with the ecology contained in the folklore of South Sumatra, (3) the social, cultural and economic background in the ecology of the story. the people of South Sumatra. The subject of this research is the folklore of South Sumatra which consists of stories. Data and information were collected from informants who know the intricacies of South Sumatran folklore. This study uses a descriptive method with a quantitative approach. The technique used in this research is content analysis, with (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions/verification. Based on the results of data analysis and discussion, it shows that the folklore of South Sumatra has ecological wisdom (1) the form of ecological wisdom contained in the folklore of South Sumatra, (2) the interaction of characters with the ecology contained in the folklore of South Sumatra, (3) background social, cultural and economic aspects that exist in the ecology of South Sumatran folklore. Folklore that has ecological wisdom is that there are 6 stories, namely Adipati Tuah Negeri (Musi Rawas), Air Balui (Musi Banyuasin), Weaving Mats (Panesak), The Origin of Seri Tanjung Village (Ogan Ilir), Bambu Kuning (Lematang), and stems of Kandis at the Base of the Baths (Panesak).